UiPath Administration and Support Guide Learn Industry-Standard Practices for Uipath Program Support and Administration Activities - Asokan, Arun Kumar (Packt Publishing, Limited, 2022)
UiPath administration, support, maintenance, monitoring, and deployment activities are mandatory and more challenging than developing bots. This is a major issue for many firms that are looking to scale their RPA programs. This book will help in training new UiPath users/resources involved in administration and support tasks to address existing skill gaps in RPA market. The book starts with an introduction to the UiPath Platform. You'll learn how to set up UiPath Platform administration, support, monitoring, reporting, deployment, and maintenance. After that, you'll cover advanced topics, such as, using the orchestrator API for support operations, security, and risk management. In addition to this, best practices for each of the topics will be covered. By the end of this book, you will have the knowledge you need to work on the support and monitoring of UiPath programs of any size.